Predictors of futile recanalization in basilar artery occlusion patients undergoing endovascular treatment: a post hoc analysis of the ATTENTION trial - Yi, Tingyu; Li, Kai; Lin, Xiao-hui; Lin, Ding-lai; Wu, Yan-Min; Pan, Zhi-nan; Zheng, Xiu-fen; Chen, Rong-cheng; Zeng, Guoyong; Chen, Wen-huo (Frontiers in Neurology, 2023)
Background Few studies have focused on factors associated with futile recanalization in patients with an acute basilar artery occlusion (BAO) that was treated with modern endovascular therapy (EVT). The aim of this study was to explore the factors associated with futile recanalization in patients with an acute BAO presented within 12 h. Methods This is a post-hoc analysis of the ATTENTION trial (The Trial of Endovascular Treatment of Acute Basilar-Artery Occlusion, ClinicalTrials.gov, number NCT 04751708). Demographics, clinical characteristics, acute stroke workflow interval times, and imaging characteristics were compared between the futile recanalization and favorable recanalization groups. The favorable outcome was defined as a modified Rankin scale (mRS) score of 0–3 at 90 days, successful reperfusion was defined as thrombolysis in cerebral infarction (TICI) 2b and 3 on the final angiogram, and futile recanalization was defined as failure to achieve a favorable outcome despite successful reperfusion. A multivariate analysis was performed to identify the predictors of futile recanalization. Results In total, 185 patients were included in the final analysis: 89 (48.1%) patients had futile recanalization and 96 (51.9%) patients had favorable recanalization. In the multivariable logistic regression analysis, older age (OR 1.04, 95% CI 1.01 to 1.08, p = 0.01) and diabetes mellitus (OR 3.35, 95% CI 1.40 to 8.01, p = 0.007) were independent predictors of futile recanalization. Conclusion Futile recanalization occurred in nearly half of patients with acute BAO following endovascular treatment. Old age and diabetes mellitus were identified as independent predictors of futile recanalization after endovascular therapy for acute BAO.